Solvent and solvation effects on reactivities and mechanisms of phospho group transfers from phosphate and phosphinate esters to nucleophiles - Onyido, Ikenna; Obumselu, Onyeka F.; Egwuatu, Chinyelu I.; Okoye, Nkechi H. (Frontiers in Chemistry, 2023)
Organophosphorus esters fulfil many industrial, agricultural, and household roles. Nature has deployed phosphates and their related anhydrides as energy carriers and reservoirs, as constituents of genetic materials in the form of DNA and RNA, and as intermediates in key biochemical conversions. The transfer of the phosphoryl (PO3) group is thus a ubiquitous biological process that is involved in a variety of transformations at the cellular level such as bioenergy and signals transductions. Significant attention has been paid in the last seven decades to understanding the mechanisms of uncatalyzed (solution) chemistry of the phospho group transfer because of the notion that enzymes convert the dissociative transition state structures in the uncatalyzed reactions into associative ones in the biological processes. In this regard, it has also been proposed that the rate enhancements enacted by enzymes result from the desolvation of the ground state in the hydrophobic active site environments, although theoretical calculations seem to disagree with this position. As a result, some attention has been paid to the study of the effects of solvent change, from water to less polar solvents, in uncatalyzed phospho transfer reactions. Such changes have consequences on the stabilities of the ground and the transition states of reactions which affect reactivities and, sometimes, the mechanisms of reactions. This review seeks to collate and evaluate what is known about solvent effects in this domain, especially their effects on rates of reactions of different classes of organophosphorus esters. The outcome of this exercise shows that a systematized study of solvent effects needs to be undertaken to fully understand the physical organic chemistry of the transfer of phosphate and related molecules from aqueous to substantially hydrophobic environments, since significant knowledge gaps exist.